2017
DOI: 10.1002/mrd.22853
|View full text |Cite
|
Sign up to set email alerts
|

Tankyrase inhibition regulates corpus luteum development and luteal function in gonadotropin‐treated rats

Abstract: Tankyrases are physiological regulators of Axin, a protein involved in several cellular processes, including Wnt signaling. Here, we investigated the effect of a specific Tankyrase inhibitor (XAV939) in follicular-luteal dynamics, and its possible relationship with ovarian vascular development. Studies were designed to analyze the effect of intrabursa administration of XAV939 in gonadotropin-treated prepubertal rats. In particular, we examined follicle and corpus luteum development, steroidogenesis, angiogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…In breast cancer cells, XAV939 has also been observed to inhibit cell growth, and, in concordance with our findings in rat corpus luteum, to increase Axin protein levels (the limiting factor of the β‐catenin destruction complex) and to decrease Wnt‐induced transcriptional activity (Accialini et al, ; Bao et al, ). Regarding ICG‐001, the only study performed in ovarian cancer cells showed that ovarian cancer initiating cells treated with ICG‐001 are more sensitive to cisplatin, and that this inhibitor also decreases stem cell frequency in platinum‐resistance cells (Nagaraj et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…In breast cancer cells, XAV939 has also been observed to inhibit cell growth, and, in concordance with our findings in rat corpus luteum, to increase Axin protein levels (the limiting factor of the β‐catenin destruction complex) and to decrease Wnt‐induced transcriptional activity (Accialini et al, ; Bao et al, ). Regarding ICG‐001, the only study performed in ovarian cancer cells showed that ovarian cancer initiating cells treated with ICG‐001 are more sensitive to cisplatin, and that this inhibitor also decreases stem cell frequency in platinum‐resistance cells (Nagaraj et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Accialini et al demonstrated that in vivo ovarian inhibition of the Wnt signaling pathway via intrabursal injections of small molecule inhibitors resulted in impaired corpus luteum development, decreased STAR and circulating progesterone. Notably, this work also linked Wnt signaling to the critical process of luteal angiogenesis by demonstrating decreased expression of ovarian VEGF isoforms after Wnt pathway inhibition 27 . Moreover, as further evidence of crosstalk between these important pathways, inhibition of Wnt/β-catenin in vitro in cultured rat corpora lutea stimulated Notch signaling (via an increase in HES expression), suggesting a mechanism by which interactions between the critical Notch and Wnt pathways can promote progesterone signaling 28 .…”
Section: Notch Wnt and Gata Signaling Pathway Interactions Further Regulate Progesteronementioning
confidence: 94%